Dinamika regional ASEAN yang mendorong pembentukan ASEAN Corporate Social Responsibility Network (ACN) - Azzahra, Salwa (Economic Military and Geographically Business Review, 2024)
The rapid development of globalization has triggered increased free trade and, at the same time, strengthened the role of Multinational Corporations (MNCs) in supporting global economic growth. The Southeast Asia region, with its impressive market potential and Gross Domestic Growth (GDP), is the main attraction for MNCs in investing capital and developing their markets in this region. However, this great economic success also presents challenges in the form of negative impacts on the environment and society. A condition of dualism in development emerged, where MNCs contributed to rapid economic growth but often resulted in environmental degradation and social dislocation. Therefore, it is important to ensure that the economic growth generated by MNCs is carried out responsibly so that it does not harm the environment and local communities. Corporate Social Responsibility (CSR) is important in overcoming these challenges in Southeast Asia. This region has a strategic role in the global economy, abundant natural resources, and various industrial sectors that face employment problems. A number of steps have been taken to implement CSR, including increasing awareness, learning, and regulation at national and regional levels. This creates a strong foundation for promoting responsible CSR practices in Southeast Asia, which will help maintain sustainable economic growth, protect the environment, and improve the well-being of local communities.